The Role of Parents in Children Who are Running in With The Law - Astuti Nur Fadillah; Asrul Nur Iman; Hardi Shofian (JURNAL BELO, 2022)
The study aims to describe the role of parents in children who run in with the law. It employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with the research objects. The findings showed that parents’ role in children who run in with the law is important because they are responsible for building children’s character and the communication patterns they apply to determine how close they are. The communication patterns applied by parents when talking with the children who run in with the law are various, including permissive and authoritarian.